The GP Programming System - Manning, Greg; Plump, Detlef (Electronic Communications of the EASST, 2008)
We describe the programming system for the graph-transformation language GP, focusing on the implementation of its compiler and abstract machine. We also compare the system's performance with other graph-transformation systems. The GP language is based on conditional rule schemata and comes with a simple formal semantics which maps input graphs to sets of output graphs. The implementation faithfully matches the semantics by using backtracking and allowing to compute all possible results for a given input.